1936
DOI: 10.1098/rspb.1936.0038
|View full text |Cite
|
Sign up to set email alerts
|

A convenient method for obtaining bovine arterial blood

Abstract: The value, both academic and practical, of accurate knowledge regarding the mechanism of mammary secretion requires no emphasis. Our relative ignorance of what is actually going on in the mammary gland during its activity has been justly lamented from time to time by several writers. Attempts have recently been made to remedy this lack of knowledge, particularly in regard to the nature of the precursors, in the blood as it reaches the gland, of the characteristic milk constituents. It is with a major point in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1937
1937
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The results indicate that the arteriovenous difference for glucose can account for most if not all that observed for total reducing substances by other workers (Graham et al 1936;Shaw 1943). In the goat, much of the glucose taken up by the mammary gland is utilized for the production of lactose and glycerol as has been demonstrated in isolated perfused goat udders (Hardwick, Lin~ell, and Mepham 1963).…”
Section: Disoussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The results indicate that the arteriovenous difference for glucose can account for most if not all that observed for total reducing substances by other workers (Graham et al 1936;Shaw 1943). In the goat, much of the glucose taken up by the mammary gland is utilized for the production of lactose and glycerol as has been demonstrated in isolated perfused goat udders (Hardwick, Lin~ell, and Mepham 1963).…”
Section: Disoussionmentioning
confidence: 48%
“…Although it islmown that large amounts of plasma triglycerides are taken up and incorporated into milk fat by the mammary gland of the lactating· goat (Barry et al 1963;Lascelles et al 1964) the situation is not as clear for the cow. Arteriovenous studies have demonstrated an uptake of plasma neutral lipids (glycerides and possibly cholesterol esters) by the mammary gland of the cow (Lintzell 1934;Graham, Kay, and McIntosh 1936;Voris, Ellis, and Maynard 1940;McClymont and Vallance 1962) but have not shown any uptake of phospholipids. However, recent experiments with a lactating cow, which was given 14 0_ and 32P-Iabelled piasma lipids intravenously, have suggested that triglycerides, cholesterol esters, and phospholipids were involved in the transport of fatty acids to the )llammary gland.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a stranger in addition to the experimenter did not appear to upset them. These precautions were taken because it has been shown in the cow that the disturbance of obtaining arteriovenous samples without local anaesthesia may seriously alter the blood composition, chiefly in respect of haemoglobin and fat (Graham, Kay & McIntosh, 1936;Shaw & Petersen, 1939). The maximum arteriovenous difference for haemoglobin or haematocrit was 3 00 and on average was less than 0-5 % in these experiments.…”
Section: Methodsmentioning
confidence: 99%